Domestic Violence: An Additive to COVID-19 Crisis. Issue 1 (June 2021) - Dehury, Ranjit Kumar; Samal, Janmejaya
The pandemic of COVID-19 is one of its kind in the history of pandemics around the world. Apart from creating ripples in its de facto biomedical spheres it also created a whole lot of social problems around the globe. The very common preventive measures that it advocates for such as physical distancing, quarantine and isolation created problems in several of the societies. These measures created problems of social stigma, discrimination, racism and others. In addition, lockdowns imposed by several governments around the globe made people stay at home without attending workplaces. As the lockdowns were stringent and continued for protracted period that led to several forms of domestic violence around the globe. Deviations in routine work life, sitting frivolously at home, use and abuse of different substances coupled with economic imbalance in families led to many different forms of intimate partner and nuptial violence in families. Many a time it happened so that the women could not access the help owing to above mentioned preventive measures that by default has to be imposed upon the citizens and they have to stay longer with the perpetrator without help. Many a time the woman cannot even leave away the perpetrator and take help in other places as she has other family liabilities and responsibilities of caring for the children and other family members. In addition, owing to the very nature of transmission of this disease they were not even entertained by authorities to stay at shelter homes in the name of physical distancing. This article discusses the impact of COVID-19 and resultant domestic violence in an Indian context.